Oral antipathogenic and antiviral properties of Boesenbergia rotunda (L.) Mansf. Extracts with panduratin A as active compound - Donruedee Sanguansermsri, Phanchana Sanguansermsri, Kittisak Buaban, Rungtip Kawaree, Ian Fraser, Nalin Wongkattiya (Journal of Applied Pharmaceutical Science, 2024)
This study investigated the anti-oral pathogen and anti-human coronavirus properties of Boesenbergia rotunda, a traditional Thai medicinal plant used for treating oral diseases. Boesenbergia rotunda Crude extracts (CBR) and B. rotunda fractionated extracts (FBR) of B. rotunda were obtained and analyzed. Panduratin A, present in both CBR and FBR, was found to play a key role in their antimicrobial efficacy. Both the extracts of B. rotunda exhibited significant antimicrobial activity against Streptococcus mutans, Streptococcus pyogenes, Streptococcus sobrinus, and Candida albicans with minimum inhibitory concentration and minimum bactericidal concentration ratios demonstrating their effectiveness. Furthermore, both extracts showed a potent and direct inhibitory effect against human coronavirus 229E, with nearly 99.99% efficacy and a 4-log reduction in viral activity at a concentration of 1,600 μg/ml within 30 minutes. This study demonstrates the potential of B. rotunda as an antiviral and antipathogenic agent, with panduratin A as a bioactive compound. FBR is more potent than CBR against oral pathogens. These findings suggest that B. rotunda is a promising herbal medicine for treating oral diseases and viral infections.
Keywords: Boesenbergia rotunda, panduratin A, anti-oral pathogens, anti-human Coronavirus, herbal extract